SPE Improved Oil Recovery Conference 2016
DOI: 10.2118/179607-ms
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Factors Influencing Polymer Hydrodynamic Retention in Porous Media

Abstract: Hydrodynamic retention is one of the contributors to polymer loss in porous media. In this study, effects of flow rate, polymer molecular weight, and core permeability on hydrodynamic retention were investigated. To quantify hydrodynamic retention, injection of two identical polymer banks at different rates separated by 100 pore volumes of brine flushing was performed. Three HPAM polymers with molecular weights of 6 -8 million, 12 million, and 20 million Daltons were tested in a 135 mD sandstone core and xanth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 11 publications
0
15
1
1
Order By: Relevance
“…The increase in hydrodynamic retention for lower M W polymer is suggesting that more polymer molecules will reside in a stagnant zone if their size is small. However, the results are different than the once which were observed by Chen et al [27]. The difference can be explained on the basis of the order of magnitude difference in permeability of the cores in the two studies.…”
Section: Resultscontrasting
confidence: 84%
See 1 more Smart Citation
“…The increase in hydrodynamic retention for lower M W polymer is suggesting that more polymer molecules will reside in a stagnant zone if their size is small. However, the results are different than the once which were observed by Chen et al [27]. The difference can be explained on the basis of the order of magnitude difference in permeability of the cores in the two studies.…”
Section: Resultscontrasting
confidence: 84%
“…The hydrodynamic retention for HPAM polymers was fairly reported in the literature [27,28]. So far, there is no study reported the hydrodynamic retention performance of the sulfonated polymers.…”
Section: Introductionmentioning
confidence: 97%
“… The packing and ageing methodology have a significant impact on the overall results [ 24 ]. Retention can be flow rate dependent, especially in low permeability rock [ 16 , 25 ]. The correlation between retention values and inaccessible pore volume in the core is still unclear [ 18 ].…”
Section: Determination Of Retention: Review Of Procedures and Challengesmentioning
confidence: 99%
“…and 12A5 were used for the retention experiments 1 and 2, performed with HPAM 3230S solutions, respectively. These samples were selected from their petrophysical similarities with the samples used in the previous retention works using the polymer HPAM 3230S (Zheng et al, 2000;Zhang and Seright, 2014;Zhang and Seright, 2015;Wan and Seright, 2016;Chen et al, 2016). .…”
Section: Dynamic Retention Tests Hpam 3230s Experiments Sandstone Samentioning
confidence: 99%